The implementation gap in waste management: A study of discrepancies in awareness, attitude, and practice - Mohammad Roy Thoriqul Haq (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Proper household waste management is essential to maintain environmental quality, especially in densely populated areas such as student boarding houses. University students, as part of the educated population, play a crucial role in promoting sustainable waste practices. However, the gap between environmental awareness and actual waste management behavior among students remains a significant challenge. Methods: This study employed a descriptive quantitative survey approach to analyze the awareness and attitudes of Universitas Negeri Semarang (UNNES) students living in boarding houses toward household waste management. Data were collected through a self-administered online questionnaire distributed to 53 respondents and analyzed using descriptive statistical methods. Findings: The results revealed that most respondents demonstrated high awareness of environmental and household waste issues, with more than 80% agreeing or strongly agreeing that waste sorting and recycling are essential. Nevertheless, their active participation in implementing waste management practices was still limited, mainly due to lack of facilities and motivation. Conclusion: The findings indicate that while awareness and attitudes are generally positive, the translation of this awareness into consistent waste management behavior remains inadequate. Novelty/Originality of this article: This study provides a focused analysis of environmental awareness and attitudes within the context of student boarding life, offering insight into behavioral gaps that can inform targeted environmental education and campus sustainability programs. However, this study is limited by its relatively small sample size and descriptive focus, which may affect the generalization of the findings. Despite this, the results provide practical implications for developing targeted environmental programs and waste management initiatives within university student communities.